Correction to: A study on using custom 3D-printed tongue bites for radiotherapy patients with oral tongue carcinoma - Muhammad Furqan Zulqurnain; Haris Arif; Misbah Batool; Nouman Amjad; Robin Hill (Physical and Engineering Sciences in Medicine, 2026)

A study on using custom 3D-printed tongue bites for radiotherapy patients with oral tongue carcinoma - Muhammad Furqan Zulqurnain; Haris Arif; Misbah Batool; Nouman Amjad; Robin Hill (Physical and Engineering Sciences in Medicine, 2026)
Oral cavity cancers are a debilitating form of head and neck cancer with high rates of mortality. Radiotherapy is one of the main forms of treatment but relies on minimizing doses that are delivered to organs at risk and considering any motion in the mouth. One solution is to use a block within the mouth which acts to reduce motion and decreases tissue heterogeneity. In this work, we developed a process for designing a customized tissue-equivalent 3D-printed tongue bite and evaluated its impact on the radiation treatment. Six patients with stage III or IV oral cancer were involved. Computed tomography (CT) images for each patient were acquired with currently used Styrofoam tongue bites within the mouth. The designs of 3D tongue bites were prepared using those CT images and then printed on an SLA printer using F80 resin which is a tissue-equivalent and biocompatible material. Secondary CT images were then acquired for each patient with the 3D tongue bites to have a dosimetric comparison. Volumetric-modulated arc therapy (VMAT) planning was carried out for individual patients on both CT images. Plan parameters, fractionation scheme and optimization priorities were all kept the same. The radiotherapy plans utilizing 3D tongue bites showed better PTV coverage and reduced D max ( p = 0.028). Doses to organs at risk (OARs) including brainstem, parotid glands and hard palate were also reduced ( p < 0.028) except for the spinal cord ( p > 0.05). The dose conformity and homogeneity were also improved ( p = 0.028 and p = 0.044 respectively). All patients reported that the 3D tongue bites were soft, conformal to the oral cavity, comfortable and did not cause any gag reflex. We conclude that the 3D tongue bite is a useful utility that improves the treatment of patients with oral cancer.

Hydrothermal synthesis of novel Mn3O4-Nd2O4 nano-hybrid as bi-functional electrocatalyst for water splitting - Muhammad Ibrar; Iram Manzoor; Mostafa A. Ismail; Misbah Shareef; Habiba Batool; Sana Ben Khalifa; Saleh Chebaane; Zeineb Klai (Fuel, 2026)

Wetland Transformation and Waterfowl Decline: Linking Habitat Change to Northern Pintail Losses in Punjab - Nayyar Batool; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Misbah Sarwar; Javaria Ikram; Naima Huma Naveed; Iram Inayat; Shaheen Riaz; Hakim Bibi (Environmental Management, 2026)

Impact of Gene–Smoking Interaction on Risk of Atherosclerosis: Molecular Study of Prothrombin (F2) Gene rs1799963 G/A Polymorphism in Atherosclerotic Patients - Farrakh Ali Abbas; Shazia Batool; Moazma Hina; Tayyba Khalid; Amna Aman; Fazli Rabbi Awan; Misbah Hussain (Cardiovascular Toxicology, 2025)

Proactive risk management should be mandatory for the setup of new techniques in radiation oncology - Johnson Yuen; Misbah Batool; Clive Baldock (Physical and Engineering Sciences in Medicine, 2024)

Characterization and Utilization of Cow Manure Biochar as Soil Amendment for the Management of Northern Corn Leaf Blight - Misbah Batool Zahra; Bakhtawar Fayyaz; Zill-E-Huma Aftab; Adnan Akhter; Tehmina Bahar; Waheed Anwar; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2022)

Mitigation of Degraded Soils by Using Biochar and Compost: a Systematic Review - Misbah Batool Zahra; Bakhtawar Fayyaz; Zill-E-Huma Aftab; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2021)

Morpho-molecular identification of Alternaria alternata causing leaf spot on loquat in Pakistan - Muhammad Fahim Abbas; Farah Naz; Sana Batool; Misbah Iqbal Qamar; Anam Moosa (Journal of Plant Pathology, 2020)